Financial valuation, application of the discounted cash flow method - Guacho Guado, Jessenia Paola; Rodríguez Ulcuango, Olga Maritza; Elizalde Marín, Letty; Alvear, Paulina Fernanda (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December), 2021)
The objective of this research is to generate a business financial valuation through a practical orientation of the discounted cash flow methodology and the clearing of questions about the estimation of the value and its usefulness. Its application was directed to the company Tannery Tungurahua limited liability company, where it was necessary to evaluate its financial performance in the leather and leather sector, determining financially important parameters such as: the historical analysis of the company, cost of capital, cost of debt and the present value of the cash flows, under these variables the value of the company is established for 14’167,763.48, from an equity of 2’709,391.84; reaching the conclusion that the valuation of companies becomes a fundamental instrument for the correct decision-making and application of financial strategies, which allows it to be included in new market segments and to determine its position vis-à-vis its competitors and investors.